Performance Evaluations for Orthogonal Handshaking Authentication Mechanism (OHASM) in Secure Cloud Storage - Sirajudeen, M. Mohamed; Subramanian, K. (Asian Journal of Science and Applied Technology, 2018)
In general, the cloud computing contributes its wide services in effective resource utilization among vendors. To share the resources such as Infrastructure as a Service (IaaS), Software as a Service (SaaS) and Platform as a Service (PaaS) in a secure channel is carried out by using different cryptographic algorithms. The demand created by IT industry provides a road map in a potential way for sharing cloud storage with variety of secure mechanism. Secure storage or security in cloud storage characterizes the convergence of the approaches in four categories: method of storage, crypto graphic algorithms, key distribution and authentication. When considering privacy risks in the cloud, as considered already within the introduction, context is very important as privacy threats differ according to the type of cloud scenario. The concepts related with secure cloud data transaction is make use of different emerging trends in real time applications such as financial transactions, medical records maintenances in health care sectors like wise. The largest part of healthcare entities is required to establish strong cloud service applications with elaborated provisions relating to security and privacy in order to fully understand their liabilities and risks as well as being able to absorb those risks in the event of non-compliance. In this research work focus a way to secure cloud data storage in transaction aspect with healthcare domain. Each and every cloud security mechanism with healthcare record maintenances is using a variety of cryptographic algorithms. Almost it describes the encrypted documents are reside in a single cloud server along with its encrypted key. This work propose a method of such secure mechanism by using Orthogonal Handshaking Authentication Mechanism (OHSAM) with a working principle of separate storage for encrypted content and its key in a cloud server.